Students’ Problems In Conducting The 8 Goals Of Plp 2 At Junior And Senior High School In Bengkulu City - Yisi Putri, Mona; Wadison, Epi (Universitas Dehasen Bengkulu, 2024)
The objective of this research was to investigate the students’ problems in conducting the 8 goals of PLP 2 at Junior And Senior High School in Bengkulu City. The researcher used a descriptive qualitative method. The subject of the study were all of the students of English program of UMB Bengkulu at seventh semester who conducted PLP in Junior and senior High School, there are seven students in junior high school and seven students in senior high school in bengkulu city in academic year 2023 with total subject 14 students. The researcher used questionnaire to investigate the students’ problems in conducting the 8 goals and components of the objectives PLP 2 at Junior High School in Bengkulu City. the findings, it can be concluded that the students’ problems in conducting the 8 goals of PLP 2 at Junior And Senior High School in Bengkulu City in Academic Year 2023 were (1) Examine the curriculum and learning tools used by teachers; (2) Examine the learning strategies implemented by the teacher; (3) Examine the Evaluation System implemented by the teacher; (4) Assist teachers in developing lesson plans, learning media, teaching materials, and evaluation tools; (5) Examine the use of information and communication technology in learning; (6) Teaching training under the guidance of tutor teachers and PLP II supervisors, with the aim of experiencing the learning process firstly, as well as strengthening the identity of prospective educators.